If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -5(x + 3) + -1(7x + -1) = 3 Reorder the terms: 8x + -5(3 + x) + -1(7x + -1) = 3 8x + (3 * -5 + x * -5) + -1(7x + -1) = 3 8x + (-15 + -5x) + -1(7x + -1) = 3 Reorder the terms: 8x + -15 + -5x + -1(-1 + 7x) = 3 8x + -15 + -5x + (-1 * -1 + 7x * -1) = 3 8x + -15 + -5x + (1 + -7x) = 3 Reorder the terms: -15 + 1 + 8x + -5x + -7x = 3 Combine like terms: -15 + 1 = -14 -14 + 8x + -5x + -7x = 3 Combine like terms: 8x + -5x = 3x -14 + 3x + -7x = 3 Combine like terms: 3x + -7x = -4x -14 + -4x = 3 Solving -14 + -4x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -4x = 3 + 14 Combine like terms: -14 + 14 = 0 0 + -4x = 3 + 14 -4x = 3 + 14 Combine like terms: 3 + 14 = 17 -4x = 17 Divide each side by '-4'. x = -4.25 Simplifying x = -4.25
| x/9+3=40 | | 4.2x=-4(0.6-1.2) | | 5y^2+40y-32=0 | | 80/64 | | s+3+s-3=s+1+s+5+s+3 | | 7x-3x+7=3(x-4)+20 | | 13/15=21/X | | -43/2x^(3/2)=0 | | 2k+3-5(k+7)=0 | | 3+4x-9=6x-4+12 | | X^3-6X^2-9X-4=0 | | 6+-8/2= | | 2X-3=10-5X+2-X | | x+4-3x=4+12x | | 12=juan | | 5(3-x)-2(4-3x)=11-2(x-1) | | 2x^5y2/3x^2y^5 | | juan=gay | | d=-8-17 | | 6x-4=12-9x | | 4x-7=2x-8 | | 2x-4+12=3x-4+2 | | 3/4(2/3)+5/3= | | 6-4(x+3)=2(x-1) | | (X*x)+6x+9=0 | | 4w+4=-4 | | (x*x)-5x+4=0 | | X+x+5x-6=0 | | 3m-9=11 | | x+5+3x=49 | | 1=.30X+.65X | | 67-(3/4)x=85 |